EMPLOYEE‐LED INNOVATION. Issue 2 (14th May 2013) - Birkinshaw, Julian; Duke, Lisa
<x xml:space="preserve">Abstract</x> How can employees take the lead in innovation?Julian Birkinshaw and Lisa Duke went in search of employee‐led innovation and found some inspiring examples.